Considerations over the Italian road bridge infrastructure safety after the Polcevera viaduct collapse: past errors and future perspectives - Fabio Bazzucchi; Luciana Restuccia; Giuseppe Ferro (Fracture and Structural Integrity)
In the last four years, Italy experienced the collapse of five road bridge: Petrulla viaduct (2014), Annone (2016) and Ancona (2017) overpasses, Fossano viaduct (2017) and Polcevera (2018) bridge.